2019
DOI: 10.1146/annurev-vision-091718-014715
|View full text |Cite
|
Sign up to set email alerts
|

How Sleep Shapes Thalamocortical Circuit Function in the Visual System

Abstract: Recent data have shown that sleep plays a beneficial role for cognitive functions such as declarative memory consolidation and perceptual learning. In this article, we review recent findings on the role of sleep in promoting adaptive visual response changes in the lateral geniculate nucleus and primary visual cortex following novel visual experiences. We discuss these findings in the context of what is currently known about how sleep affects the activity and function of thalamocortical circuits and current hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 130 publications
1
17
0
Order By: Relevance
“…non-hub neurons with the least number of connections) exhibited a smaller magnitude of decrease in frequency in high-ACh state following the low-ACh state. Various in vivo studies have shown that SWS-mediated frequency dependent changes in firing rates within the visual cortex of mice led to the homogenization of spiking frequency of hippocampal neurons (Clawson et al, 2018;Durkin and Aton, 2019;Miyawaki et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…non-hub neurons with the least number of connections) exhibited a smaller magnitude of decrease in frequency in high-ACh state following the low-ACh state. Various in vivo studies have shown that SWS-mediated frequency dependent changes in firing rates within the visual cortex of mice led to the homogenization of spiking frequency of hippocampal neurons (Clawson et al, 2018;Durkin and Aton, 2019;Miyawaki et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The artifact-free EEG segments analysed for estimating power band content in five frequency bands of interest were considered: theta (4-8 Hz), alpha (8)(9)(10)(11)(12), low beta (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), high beta (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and gamma (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). Power densities were estimated applying a Hammingwindowed FFT on 4 sec consecutive EEG segments and log-transformed (dB).…”
Section: Monocular Deprivation Morning Eeg Processingmentioning
confidence: 99%
“…Importantly, this effect was specifically induced by sleep: two hours of dark exposure after MD did not prevent the decay of the effect. Results from animal models have shown that NREM sleep consolidates ocular dominance plasticity during the critical period 32,34,49 . This sleepdependent consolidation relies on Hebbian mechanisms and it is mediated by synaptic potentiation through increased NMDAR and PKA activity 32 and decreased GABAergic inhibition 34 .…”
Section: Role Of Sleep In Visual Plasticity Consolidationmentioning
confidence: 99%
See 2 more Smart Citations